Plasma lipids as risk factors in relapsing nephrotic syndrome - Sitti Aizah Lawang; Syarifuddin Rauf; J. S. Lisal; Husein Albar; Dasril Daud (Indonesian Pediatric Society Publishing House, 2016)
Background Nephrotic syndrome is primarily a pediatric disorder and is 15 times more common in children than in adults. Relapse rate after corticosteroid discontinuation is 39 - 59%. Hyperlipidemia is an important characteristic of nephrotic syndrome. The plasma concentrations of cholesterol, triglyceride, LDL, and VLDL are increased. Persistent hyperlipidemia after remission can be found in frequent relapse nephrotic syndrome. Objective To determine plasma lipids as risk factor for relapsing nephrotic syndrome. Methods Thirty children with nephrotic syndrome were included in this cohort study from March 2005 until June 2007 at Wahidin Sudirohusodo Hospital, Makassar. Thirty children without renal disease were enrolled as control. Blood specimens were collected to determine plasma lipids (cholesterol, triglyceride, LDL, and HDL) levels and LDU HDL ratio. Plasma lipids were examined in the acute and remission phases. Follow up was carried out six months after remission to determine the occurrence of relapsing nephrotic syndrome. Results Of 30 nephrotic syndrome patients, 12 had relapsed. There were highly significant differences in total cholesterol, HDL, LDL, triglyceride, and LDL/HDL ratio between acute nephrotic syndrome and nephrotic syndrome in remission. There were no significant differences in cholesterol, LDL, triglyceride, LDL! HDL ratio between nephrotic syndrome in remission and control. There was also no significant difference in the incidence in relapse between first attack and nephrotic syndrome with more than two attacks. Acute lipid fraction levels were not risk factors in relapsing mephrotic syndrome. Remission triglyceride level was a risk factor in relapsing nephrotic syndrome with the prevalence risk of 5.2 and CI 95% of 1.06 to 25.3. Conclusion Persistent hypertriglyceride in remission phase is associated with an increased risk of relapse in children with nephrotic syndrome.